Working conditions teaching in the Degree in Rural Education (LEdoC) in the state of Amapá (2014-2020) - Vanessa Lima dos Santos Assunção Assunção; Sidney da Silva Lobato (Universidade Federal do Norte do Tocantins, 2024)
This article analyzes the working conditions of teachers in the Degree in Rural Education (LEdoC) at Campus Mazagão at the Federal University of Amapá (Unifap). Our study is scoped to the period since the implementation of this LEdoC, in 2014, until the moment of suspension of its face-to-face activities, in early 2020. The research problem is: what were the teaching working conditions at LEdoC, during its first years of existence? The examination of these conditions took place through oral history interviews and documentary research. The results show that the State, when executing educational policies for the LEdoC, did not guarantee a minimum structure to the Campus Mazagão and, as a result, the teaching work carried out there was precarious and intensified.